Institutional Arrangement and Policy for Improving Competitivenes and Innovation in Local Government Investment - Sanusi, Anwar; Dwiputranti, Septiana (UI Scholars Hub, 2013)
There are three specific objectives outlined in this paper, the first objective is to identify and describe existing condition of institutional arrangement of public services in several local governments, the second objective is to examine problems and challenges in providing public services in the areas of investment, the last is to provide recommendations on institutional models and strategies or innovations which can be applied in order to improve performance in investment services; undertanding how regional goverment institutions can contribute significantly to improve investment for economic growth. Qualitative method was employed to evaluate the effectiveness of increasing customer satisfactions, reducing red-tape, and improving coordination amongst government institutions, an in- depth interviews conducted with resource persons as respresentatives from stakeholders, including government officials, businessmen (entrepreneurs), and experts from local universities. By evaluating City Government of Batam as the best practice in the institutional arrangement for investment, the main potential contribution of this study is to provide valid information about the most crucial problems and challenges in institutional arrangement for investment affairs in local government to which their investment target could be achieved by using the institutional model provided.